Food processing technology : principles and practice - Fellows, P. 1953- (CRC Press ; Woodhead Pub., 2009)
The first edition of Food processing technology was quickly adopted as the standard text by many food science and technology courses. This completely revised and updated third edition consolidates the position of this textbook as the best single-volume introduction to food manufacturing technologies available. This edition has been updated and extended to include the many developments that have taken place since the second edition was published. In particular, advances in microprocessor control of equipment, 'minimal' processing technologies, functional foods, developments in 'active' or 'intelligent' packaging, and storage and distribution logistics are described. Technologies that relate to cost savings, environmental improvement or enhanced product quality are highlighted. Additionally, sections in each chapter on the impact of processing on food-borne micro-organisms are included for the first time. Introduces a range of processing techniques that are used in food manufacturingExplains the key principles of each process, including the equipment used and the effects of processing on micro-organisms that contaminate foodsDescribes post-processing operations, including packaging and distribution logistics.
Keywords: Food industry and trade.; elektronické knihy; electronic books